The Concept of Integrity and Its Application to Engineering Ethics - Wajszczyk, Piotr (Annales. Etyka w Życiu Gospodarczym, 2014)
Integrity is a common and well established concept in the ethical vocabulary. It is also being used in various codes of ethics, and investigated by means of various methods. However a review of the contemporary reference literature reveals various meanings associated with this term, which is followed by its variable applicability. It is mentioned among the desirable virtues possessed by the professionals. In various Polish codes of engineering ethics there is an absence of the integrity concept, at least comprehended as fully as it is in the ethics literature. The paper contains an analysis of the meaning of integrity in English and its translations into Polish in selected codes of engineering ethics. The scopes of the used terms are compared and in result it is postulated that some initiatives be undertaken in order to clarify the discrepancies existing in various engineering codes of ethics around the professional integrity concept.